Regulatory Quality and Competition Policy - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (World Bank, Washington, DC, 2017)
Regulatory reform and competition policy are two important and inter-related areas of regulatory policy and public administration. Both can play a key role in improving the quality of regulation, and creating healthy and competitive markets and an attractive investment climate. This in turn leads to greater economic growth, employment and incomes. Part one of this paper discusses definitions and key issues associated with regulation, regulatory quality, and competition policy. This discussion focuses on competition policy as it relates to restrictions on competition and also pro-competitive regulation, which involves protecting consumers through economic regulation. Part two of this paper considers institutions and processes for implementing regulatory quality and competition policy agendas, including regulatory agencies, regulatory reform bodies, competition authorities and broader regulation-making processes. Part three notes the importance of assessing competition policy issues on a case-by-case basis and identifies the main objectives and features of competition policy. This includes a discussion about when competition policy issues are likely to play an important role in regulatory assessment and reform. Part four considers mechanisms for coordinating- where appropriate-competition policy and regulatory quality assessments, including undertaking competition assessments and providing advice to decision makers.